2017
DOI: 10.6061/clinics/2017(06)05
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Findings of the Bifid Median Nerve and Persistent Median Artery in Carpal Tunnel: A Preliminary Study in Chinese Individuals

Abstract: OBJECTIVE:The aim of this study was to investigate the prevalence of anatomic variations of the bifid median nerve, persistent median artery and persistent median vein in Chinese individuals and their relationship with carpal tunnel syndrome.METHODS:One hundred and sixty median nerves were examined using ultrasonography and colour Doppler ultrasonography. The location, shape, and size of the bifid median nerve, persistent median artery and persistent median vein were recorded. The cross-sectional area of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 17 publications
(23 reference statements)
6
39
1
2
Order By: Relevance
“…The topography of the PMA and MN along the forearm in the present case corroborates Chen et al and seems to be very constant. 12 Nevertheless, such topography changes in the carpal tunnel in a variable way: anterior, anterolateral or anteromedial position, which is similar to the present case. 10,12 Thus, this makes a preoperative ultrasound an essential tool to avoid iatrogenic injuries during the surgical procedure in the CTS.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The topography of the PMA and MN along the forearm in the present case corroborates Chen et al and seems to be very constant. 12 Nevertheless, such topography changes in the carpal tunnel in a variable way: anterior, anterolateral or anteromedial position, which is similar to the present case. 10,12 Thus, this makes a preoperative ultrasound an essential tool to avoid iatrogenic injuries during the surgical procedure in the CTS.…”
Section: Discussionsupporting
confidence: 85%
“…While Pierre-Jerome et al described that the PMA was more frequent bilaterally, and when unilateral, it was more frequent in the left limb of females, 11 Chen et al reported that there is no statistical difference regarding the side of occurrence. 12 Furthermore, bilateralism was not verified in the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…(9,10) La persistencia de la arteria mediana también puede ocurrir junto con anomalías del nervio mediano. Varios autores han descrito división del nervio mediano por la arteria mediana (11) mientras que otros han informado de la aparición de arteria mediana persistente asociada con una división alta del nervio, observándose una probabilidad más elevada de coexistencia de ambas anomalías (63%), que la probabilidad de presentarse independientemente. (12) Así ocurre en nuestro caso anatómico, en el que observamos un nervio mediano bífido dividido 5 cm.…”
Section: Discussionunclassified
“…Our present findings indicate that the prominent superficial palmar branch contributed to the formation of superficial palmar arch more often when the brachioradial artery occurred. The presence of atypical arterial patterns in the upper limb can be predicted based on the Color Doppler ultrasonography, which facilitate the assessment of the origin, course, variations, and locations of both arteries and accompanying veins [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%